Development and assessment of sustained release stavudine loaded microparticles - Zindove, Chiedza Cathrine (Rhodes University, Faculty of Pharmacy, Pharmacy, 2014)
Stavudine (D4T) has been used as first line treatment for HIV/AIDS and is part of highly active anti retroviral treatment (HAART). It is an affordable medicine and its use is beneficial in resource limited settings. However D4T exhibits dose dependent side effects that may lead to non-adherence in patients. This study was undertaken to formulate, develop and manufacture a dosage form that could reduce dose dependent side effects by decreasing the dose of D4T but still exhibit antiretroviral (ARV) activity. The use of sustained release (SR) formulations of D4T that ensure constant levels of the D4T in the body would not only optimize therapy but also reduce the incidence of side effects thereby increasing patient adherence. SR microparticles containing 30mg D4T were manufactured and loaded into size 3 hard gelatine capsules prior to analysis. The D4T microparticles were manufactured by microencapsulation using non-aqueous oil-in-oil solvent evaporation approach. D4T-excipient, excipient-excipient interactions and D4T purity were assessed using Infrared Spectroscopy (IR), Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA). Copolymers synthesized from acrylic and methacrylic acid esters viz., EudragitÂ® RSPO and S100 were used as rate retardant materials and the effect of microcrystalline cellulose (AvicelÂ® PH102) on the microparticles was also investigated. Magnesium stearate was used as a droplet stabilizer and n-hexane was added to harden the microspheres formed in a liquid paraffin continuous phase. The microparticles were optimized using a Box Behnken design and Response Surface Methodology (RSM). The microparticles were characterized in terms of their flow properties and encapsulation efficiency (% EE), in addition to visualization of the surface morphology with Scanning Electron Microscopy. In vitro D4T release studies were performed using USP Apparatus III in media of different pH and the samples were analysed using a validated High Performance Liquid Chromatographic (HPLC) method with ultraviolet (UV) detection that had been developed and optimized using a Central Composite Design (CCD). The method was validated according to ICH guidelines. The IR spectra and DSC thermographs revealed that D4T exhibited thermal stability and there was no evidence of D4T-excipient and excipient-excipient interactions. The microparticles that were produced were white, free flowing and were obtained in a high yield with high encapsulation efficiency. Scanning Electron Microscopy studies revealed that the microparticles were spherical and porous in nature. In vitro D4T release extended to 12 hours and the mechanism of release was established using model dependent methods by fitting the data to a Zero order, First order, Higuchi and Hixson Crowell model. It was observed that the mechanism of D4T release was diffusion-controlled and that the data was best fitted to the Higuchi model with correlation coefficients > 0.9. The release mechanism was confirmed using the Korsmeyer-Peppas model that revealed that most of the formulations exhibited anomalous transport kinetics with the release exponent, n, ranging from 0.5<n<1.0. These data suggest that diffusion was not the only mechanism controlling D4T release and that swelling and/or polymer relaxation may contribute to the release. Model-independent analysis for comparison of dissolution profiles was undertaken and the f1 and f2 difference and similarity factor were calculated. The optimized formulation, Batch BB-018 was found to be similar to two batches (BB-005 and BB-016). The dissolution profiles were evaluated to establish which of the batches exhibited D4T release that was appropriate for SR dosage forms. In conclusion polymethacrylate copolymers were successfully used to produce SR D4T microparticles that have the potential to be used for a twice a day dosing of D4T.
Keywords: Uncatalogued